Malaysia’s graphene commercialization progress National Graphene Action Plan 2020 - Shamsul Harumain, Zakuan Azizi; Ahmad, Rezal Khairi (2018)
NanoMalaysia’s National Graphene Action Plan 2020 is supported by the country’s 11th Malaysia Plan (2016- 2020) as a catalytic support to expedite industrial adoption of graphene applications. Realizing the economic significance in the global market, more than 30 product development and pilot production projects have been initiated in the form of – government-industry-academia partnerships. These graphene based products are at the cusp of entering mainstream local and global markets.